Harald Moltke, Outstanding Painter of the Aurora: Unifying Art and Science - Peter Stauning (Current Progress in Arts and Social Studies Research Vol. 9, 2025)
This study explores the artistic and scientific contributions of Count Harald Moltke, an exceptional painter of auroras, through his work produced for the Danish Meteorological Institute during two auroral expeditions: to Akureyri, Iceland (1899–1900), and Finland (1900–1901). Organized by the Institute’s director, Adam F. W. Paulsen, these expeditions aimed to document auroral phenomena. Moltke was tasked with creating detailed colour reproductions of observed auroras, while also assisting with meteorological measurements. During the Icelandic expedition, Paulsen led the team, which included the young student Dan B. la Cour, who later became the Institute’s director. For the Finland expedition, leadership passed to la Cour due to Paulsen’s advancing age and weak eyesight. Moltke’s paintings from these expeditions remain significant, blending artistic mastery with passionate emotions and scientific documentation, and are celebrated as invaluable contributions to both art and the history of science.